2018
DOI: 10.1186/s12885-018-4960-y
|View full text |Cite
|
Sign up to set email alerts
|

Disease severity-based evaluation of utility weights for lung cancer-related health states in Korea

Abstract: BackgroundUtility weight, a measure of health-related quality of life, is used in disease burden measurements and economic evaluations. In this study, we used the visual analogue scale (VAS) and standard gamble (SG) method to determine the utility weights of lung cancer health states in South Korea from a societal perspective.MethodsSix hypothetical health states for lung cancer or a related health state reflective of disease severity were developed: 1) Stage I, 2) Stage II, 3) Stage IIIa, 4) Stage IIIB, 5) St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Lung cancer subtypes comprised one study in squamous cell lung cancer [42], three studies in NSCLC [28,43,44], and one study in general lung cancer (n = 1) [45]. Four studies reported HSUVs derived from indirect methods [28,[43][44][45], and one from direct methods [42]. Studies by Wolff et al [44] and Iyer et al [28] that only reported HSUVs for early disease or late disease are summarized in Online Resource 4.…”
Section: Lung Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Lung cancer subtypes comprised one study in squamous cell lung cancer [42], three studies in NSCLC [28,43,44], and one study in general lung cancer (n = 1) [45]. Four studies reported HSUVs derived from indirect methods [28,[43][44][45], and one from direct methods [42]. Studies by Wolff et al [44] and Iyer et al [28] that only reported HSUVs for early disease or late disease are summarized in Online Resource 4.…”
Section: Lung Cancermentioning
confidence: 99%
“…d Kim [36]: SG, hypothetical health states, general population separate study by Shen et al [43], HSUVs (based on EQ-5D-3L) in patients with NSCLC resulted in a disutility of − 0.095 for stage IV vs III. In the third study, Kim et al [42] used SG to elicit HSUVs in adults from the general population in Korea, revealing that the largest disutility occurred for stage IV vs I (− 0.350) compared with stage IV vs II (− 0.250) and stage IV vs III (− 0.105). Consistent results were observed in this study among subgroups based on gender, age, education level, occupation, monthly income, hospitalization, and morbidity.…”
Section: Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 24 studies were excluded from subsequent analyses . Among the excluded studies, four did not measure HRQoL in patients [72,77,81,82], nine did not use valuation by members of the general public [59,60,63,69,71,72,74,81,82], 11 did not use a choice-based method for valuation [59, 63, 65, 67-71, 74, 76, 81], and nine had missing data on one or more of these items [61,62,64,66,73,75,[78][79][80].…”
Section: Critical Appraisalmentioning
confidence: 99%
“…The weights as follows: age 55–59, 0.942; age 60–64, 0.944; age 65–69, 0.916; age 70–74, 0.880; age 75–79, 0.887; age ≥ 80, 0.829. The utility weights of health states in each cancer stage were obtained from the utility study for lung cancer-related health states in Korea ( Table 1 ) [ 31 ].…”
Section: Methodsmentioning
confidence: 99%